PRODUCT INNOVATION MEDIATES MARKET ORIENTATION EFFECT ON CULINARY MSMES MARKETING PERFORMANCE IN TERNATE CITY - Yolanda Mohungo; Laela Laela; Zandy Pratama Zain (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study is important to answer the problems faced by culinary business owners in Ternate by examining the influence of customer orientation, competitor orientation that affects business performance and trying to trace the involvement of aesthetic innovation variables as mediating variables. The type of research used in this study is explanatory research or causal study which aims to explain the relationship and influence between observed variables through hypothesis testing. The population used in this study were all culinary MSMEs in Ternate City that had been running their business for more than 1 year. The result shows that study show the indirect effect of Market Orientation toward Marketing Perfomance with Product Inovation as mediating variable is positive and significant. Also, Market Orientation towards Product Innovation and Product Innovation towards Marketing Performance are positive and significant, while Market Orientation on Marketing is negative and insignificant. In Conclustion, culinary MSMEs in Ternate City should innovate their product in order to stimulate market orientation effects on marketing performance.